Effects and limitations of superhydrophobic surfaces on the heat transfer performance of a two-phase closed thermosyphon. (September 2021) - Seo, Donghyun; Park, Jinsoo; Shim, Jaehwan; Nam, Jeonghyeon; Shin, Dong Hwan; Nam, Youngsuk; Lee, Jungho
Highlights: Internal flow pattern and condensation behavior of a superhydrophobic surface in a TPCT were investigated by the change of heat flux. Stepwise propagation of local surface flooding induced by the repetitive liquid collision was systematically analyzed. An entrainment effect of growing and jumping droplets caused by counter-current vapor flow was visually studied. Effects and limitations of the superhydrophobic condenser on the heat transfer performance of the TPCT were demonstrated using experiments and analytical models. Abstract: A two-phase closed thermosyphon (TPCT), also called a gravity-assisted heat pipe, is an efficient heat transfer device that exploits boiling and condensation phase-change phenomena to transport large amounts of heat. Recently, jumping droplet condensation on a well-designed superhydrophobic (SHPo) surface has shown superior condensation heat transfer coefficient (HTC), exceeding 380% and 30% over conventional filmwise and dropwise condensation, respectively. However, SHPo surfaces within TPCTs have shown much lower HTCs than expected, and the exact cause of this has not been investigated yet. Here, we experimentally explored the effects and limitations of a SHPo surface in a TPCT by visualizing the internal flow patterns and condensation behavior according to heat flux. We constructed a TPCT device capable of visualizing the inside and fabricated a SHPo surface on a condenser wall of the TPCT. We revealed two important condensation characteristics that limit the condenser HTC of the SHPo surface and the TPCT's heat transfer performance. At high heat fluxes (≥ 90 kW/m 2 ), the repetitive liquid collision led to an early flooding transition of the surface and a stepwise decrease in the condenser HTC. At low heat fluxes (< 90 kW/m 2 ), counter-current flow generated by the evaporation and boiling caused the drag force enough to entrain growing and jumping droplets, which interrupted the removal of condensate from the surface and limited the condenser HTC. We quantified their effects on the condenser and TPCT's heat transfer performance using experiments and analytical models.